Measurement of gaseous and particulate formaldehyde in the Yangtze River Delta, China. (1st March 2020) - Xu, Rongjuan; Li, Xin; Dong, Huabin; Wu, Zhijun; Chen, Shiyi; Fang, Xin; Gao, Jie; Guo, Song; Hu, Min; Li, Dongqing; Liu, Yuechen; Liu, Ying; et al.
Abstract: Formaldehyde (HCHO) is one of the most important intermediate products of atmospheric photochemical reactions and is also a radical source that promotes ozone formation. Given its high solubility, HCHO is likely to exist in particulate form. In this work, gaseous HCHO (HCHOg ) and particulate HCHO (HCHOp ) were separated and collected by a rotating wet annular denude (RWAD) and an aerosol growth chamber–coil aerosol cooler (AC). The collected HCHO from the RWAD and AC are measured by two online Hantzsch method-based formaldehyde analyzers. The comprehensive campaign was held in the Yangtze River Delta of China from 15 May to 18 June 2018, which is during the harvest season. Several biomass burning events were identified by using acetonitrile as a tracer. During the period influenced by biomass burning, the mixing ratios of HCHOg and HCHOp were respectively 122% and 231% higher than those during other time periods. The enhancement ratio of HCHOg to acetonitrile obtained from this work generally agrees with those from the existing literature. Biomass burning contributed 14.8% to HCHOg, but the abundant freshly discharged precursors it emitted greatly promoted the secondary production of HCHOg . We suggest that the high concentration of HCHOp during the biomass burning period was from uptake of HCHOg by aerosols during their transportation; the liquid state particles are conducive to HCHOg uptake. High relative humidity, a low particle rebound fraction f, as well as low temperatures may result in higher uptake coefficient values. Graphical abstract: Image 1 Highlights: Simultaneous online measurements of gaseous HCHO and particulate HCHO were conducted. Precursors emitted by biomass burning promoted the secondary production of gaseous HCHO. Particles in liquid state are conducive to uptake HCHO. High RH and lower temperature may result in higher uptake coefficient.